Energy efficency of chancellery building at Universiti Utara Malaysia - Jamaludin, Roslan; Mohd Nawi, Mohd Nasrun; Bahaudin, Ahmad Yusni; Mohtar, Shahimi; Tahir, Mohamad Zamhari (Akademia Baru, 2019)
There are various initiatives in ensuring the optimum and efficiency usage of energy in the government owned buildings. By complying with the MS1525:2007 standard, the energy efficiency of buildings is taken as a reference to ensure the buildings meets the current standard. This paper presents a three years energy consumption data of the Chancellery building at Universiti Utara Malaysia. This study aims to ensure that the building is able to meet the standard requirements of the Building Energy Index (BEI). Based on MS 1525:2007 any building which implements energy efficient measures can achieve the BEI of 136kWh/m2/year. Preliminary audit conducted involves a brief review of utility and building operation, observation and a walkthrough in the building. General audit has been conducted in order to get a better understanding of major energy consumption and to collect more detailed information about the operation of the building. Data from monthly energy usage and gross floor area of the building has been collected and the BEI was calculated. Recommendation on how to improve energy saving and enhancement for building performance are presented. Several energy efficiency practices that do not involve higher operation cost or without any additional cost are also introduced. By implementing some of the good energy efficiency measures in the building enable better assessment and continuous monitoring of energy usages within the university campus.